41. EVALUATION OF COMPLEMENTARY EFFECTS OF DIEBETES TREATMENT AND CANCER CELL INHIBITION USING A FERMENTED PRODUCT DERIVED FROM CASHEW APPLE AND NONI FRUITS (Vietnam Journal of Community Medicine, 2024)
Every year, approximately 5.6 million tons of cashew apples have been discarded in the local regionof Ia Grai District, Gia Lai Province. In addition to their sugar and mineral content, cashew applescontain biochemical active compounds which confer various health benefits thanks to theirantioxidative, anti-inflammatory and anti-cancer properties. Noni fruits, unfortunately, encounter acomparable outcome. Both fruits are currently considered waste products, resulting in large wastage.Objective: The objective of this study is to evaluate the hypoglycemic and anti-proliferative cancercell effects of a fermented product (NCF) derived from cashew apples and noni fruits.Method: In the study, blood glucose levels were measured using Sivalingam's (2013) methods andMosmann's (1983) method was employed to assess the anti-cancer properties,…Results: The results demonstrated that the NCF contains a substantial amount of antioxidants, whichcan directly or indirectly contribute to reducing blood glucose levels and inhibit cancer cell growth.Moreover, NCF significantly lowered blood glucose levels in mice and enhanced catalase activity inthe mice’s liver (p
Keywords: Diabetes, cancer, fermented product, NCF, cashew and noni, anacardic acid.